A brief survey on Alternative and Complementary Medicine with special reference to safety, toxins and toxicological concerns - Mohd. Wasiullah; Piyush Yadav; Akriti Yadav (International Journal of Toxins and Toxics, 2026)
Alternative and Complementary Medicine (ACM) is a wide range of healthcare practices that may be used within or alongside conventional medicine, and many of these practices are rapidly becoming accepted and integrated into the modern healthcare system. In addition to traditional medicine systems (e.g. Ayurveda, Unani Medicine, Traditional Chinese Medicine, and Homeopathy), ACM includes practices that utilize natural remedies including herbal medicine, phytotherapy, naturopathy, acupuncture, yoga, and meditation. While these therapies are often perceived as natural and therefore safe, increasing evidence shows that some preparations may contain intrinsic toxins, toxic metabolites, heavy metals or other toxic contaminants, leading to organ toxicity and adverse clinical outcomes if not properly regulated. The ACM philosophy promotes wellness, holistic care, mind–body therapies, and the use of food and/or supplements to maintain health and prevent disease, but parallel attention is required on toxicological risk, dose, quality control and potential toxic herb–drug interactions. Acceptance of ACM is largely influenced by patient preferences as well as cultural and ethnomedical factors and access. There are serious concerns regarding the safety, effectiveness, quality assurance, and regulation of many ACM practices, including the presence of toxins and toxicants due to adulteration, misidentification of plants and environmental contamination. To successfully combine these types of therapies with conventional medicine requires evidence-based medicine as well as the evaluation of clinical outcomes and potential drug–herb interactions, including their toxicological profile. To protect the health and well-being of the public and maximize the positive aspects of integrative medicine will require the establishment of standardization, toxicological evaluation and regulatory frameworks.Alternative and Complementary Medicine (ACM) is a wide range of healthcare practices that may be used within or alongside conventional medicine, and many of these practices are rapidly becoming accepted and integrated into the modern healthcare system. In addition to traditional medicine systems (e.g. Ayurveda, Unani Medicine, Traditional Chinese Medicine, and Homeopathy), ACM includes practices that utilize natural remedies including herbal medicine, phytotherapy, naturopathy, acupuncture, yoga, and meditation. While these therapies are often perceived as natural and therefore safe, increasing evidence shows that some preparations may contain intrinsic toxins, toxic metabolites, heavy metals or other toxic contaminants, leading to organ toxicity and adverse clinical outcomes if not properly regulated. The ACM philosophy promotes wellness, holistic care, mind–body therapies, and the use of food and/or supplements to maintain health and prevent disease, but parallel attention is required on toxicological risk, dose, quality control and potential toxic herb–drug interactions. Acceptance of ACM is largely influenced by patient preferences as well as cultural and ethnomedical factors and access. There are serious concerns regarding the safety, effectiveness, quality assurance, and regulation of many ACM practices, including the presence of toxins and toxicants due to adulteration, misidentification of plants and environmental contamination. To successfully combine these types of therapies with conventional medicine requires evidence-based medicine as well as the evaluation of clinical outcomes and potential drug–herb interactions, including their toxicological profile. To protect the health and well-being of the public and maximize the positive aspects of integrative medicine will require the establishment of standardization, toxicological evaluation and regulatory frameworks.
Keywords: Alternative medicine; Clinical Outcome; Complementary Medicine; Cultural and Ethnomedical Practices; Drug–Herb Interactions; Global Health Practices; Patient Preference; Public Health Impact; Regulation and Standardization; Safety and Efficacy; Toxicity; Toxicological Risk; adverse effects; herbal medicine; integrative medicine; quality control; toxins; traditional medicine